Biophysical regulation of cancer stem/initiating cells: Implications for disease mechanisms and translation. (March 2017) - Chen, Joseph; Kumar, Sanjay
Abstract: Cancer stem/initiating cells (CSCs) are a subset of tumor cells proposed to play privileged roles in seeding tumors and driving metastasis. CSCs have emerged as an increasingly important target of interest in cancer biology and therapy. Recent work has suggested that CSC maintenance and metastatic potential may be modulated by physical inputs within the tissue microenvironment, including interstitial pressure and extracellular matrix stiffness. Here we review recent progress in our understanding of CSC regulation by biophysical signals within the tumor microenvironment. While the mechanistic basis of this signaling remains incompletely understood, we discuss emerging evidence that mechanical inputs can epigenetically regulate CSC behavior and that some CSCs can evade mechanotransductive signals to more efficiently infiltrate tissue. We also describe efforts to leverage these findings to engineer culture platforms for the characterization of CSC mechanics for discovery and screening. Graphical abstract: Highlights: Cancer stem/initiating cells (CSCs) are emerging as an important target of discovery and translational efforts. Biophysical cues in the tumor microenvironment may be key regulators of CSC maintenance and tumorigenic potential. CSCs have unique mechanical properties relative to non-CSC tumor cells, which may enable high-throughput mechanical sorting. Mechanotransductive signaling pathways within CSCs may represent promising new therapeutic targets.